Seventy-Four Tools for Good Living : Reflections on the Fourth Chapter of Benedict's Rule - Casey, Michael, 1942- (Book collections on Project MUSE., 2014)
There is more in Benedict's Rule than meets the eye. Based on the rules of life of John Cassian and Saint Basil, Benedict invites readers to go further back to the scriptural basis of all Christian and monastic living and pursue a spiritual journey by the guidance of the Gospel. This book of reflections on the tools for good living is intended to be read very slowly, one section at a time. In addition to communicating reflections on each verse of chapter 4, Casey invites readers to: * Continue the process of reflection for themselves. * Apply what is written to their own lives. * Draw on their own wisdom and insight. * And, ultimately, broaden their experience of monastic spirituality.